Awareness and Health-Seeking Behaviour Regarding Japanese Encephalitis in Kurnool: A Cross-Sectional Study - Karthik S Murthy; P Sudha Kumari; K Ravi Naik; M V S Nagaraju (RGUHS National Journal of Public Health)
Introduction Despite growing concerns over the emergence of Japanese encephalitis JE it remains poorly understood mainly because the problem has been approached in a compartmentalized manner with human health animal health policy design and implementation being examined in isolated silos.Aim To determine the level of awareness and health-seeking behaviour related to JE among residents of Sriramnagar Kurnool.Methodology This cross-sectional study was conducted among 100 participants selected using simple random sampling. Institutional ethical clearance was obtained before the start of study. The study was conducted during July-August 2024. The study included consenting individuals residing in the selected locality for more than six months and it excluded the residents not willing to participate in the study or residing in that locality for less than six months. The data were collected through a pre-tested semi-structured questionnaire. Collected data were processed on MS-Excel and analyzed using SPSS.Results About 60 of the respondents were aware of Japanese encephalitis but 70 of them were unaware of its specific symptoms. Regarding the awareness about vaccination for JE only 44 of the subjects were aware of JE vaccination for children and adults. Among those aware only 52.28 had administered at least one dose of the JE vaccine to their children. About 78 of the respondents cited lack of awareness as a barrier to seeking timely healthcare.Conclusion Majority of the participants were aware of JE while very few understood its transmission and prevention. Lack of awareness was found to be a key barrier to timely health care indicating a critical need for targeted education and awareness programs in Kurnool.